The Effect of English Songs to Improve Student’s Listening Ability - Syarifah Aini Sinaga; Ahmad Muhajir; Yusnita Nasution (Medan Resource Center, 2022)
This study aims to determine the student’s listening improvement by using instructional media for English Song, students grade VIII MTs. Muhammadiyah 13 Tanjung Morawa. The lack of students’ listening ability through was caused by the learning condition which was not using media so that the learning process run so monotonous and it impact to the students anthusiasm. This case made the students felt boring. In order to achieve the goals that have been determined, then this study uses a two group pretest and posttest experimental research methods. The number of samples in this research were 20 students. The result of t-observed was 5.8 and t-table was 1.68 it means that t-observed higher than t-table. Because the result of t-observed is higher than t-table, it means that by using the media English songs can showed a significant affect on the improvement of listening VIII MTs. Muhammadiyah 13 Tanjung Morawa. The reseacher sincerely expected that enthusiasm are able to try and apply the appropriate media and in accordance with the material to be taught, one of them is the use of English song media for listening improvement.